Robert Musil and the question of science : ethics, aesthetics, and the problem of the two cultures - Mehigan, Timothy J. (Studies in German literature linguistics and culture, 2020)
"A major new study of Robert Musil by one of the world's leading Musil scholars. Musil's extraordinary works, the study reveals, emerged from the problem of the "two cultures.""--